Estratégias de midiatização das drogas: Estudo de uma campanha de prevenção às drogas promovida pela CTDIA - Chagas, Arnaldo Toni Sousa das (Universidade do Vale do Rio do Sinos, 2009)
This thesis proposes itself to investigate the mediatization of the drugs phenomenon through an ample prevention campaign developed by the NGO CTDia and by the publicity agency OpusMultipla. The focus of this research examines the strategies and operations developed, aiming for the complex nature of the campaign as it takes as references from several social fields, mainly mediatic operations. The drugs problematic, under the shape of a campaign, is seen in this thesis as an ample, complex and multifaceted phenomenon, calling attention for a strategy that is developed by non-mediatic fields, taking into account the existence and functioning of mediatization. We propose so, to know why such a solid area that deals with drugs produces a strategic handling of a campaign, with aid of mediatic operations, being contaminated by its logic in making a point of view become public. The preventive actions against drug use have existed for decades, whereas, paradoxally, its consumption increases every year. Therefore, we
Keywords: campanha publicitária; drogas; estratégias; ideologias; sentidos; midiatização; drugs; ideologies; publicity campaign; senses; strategies; mediatization; Ciências Sociais Aplicadas